Assessment of upper airways measurements in patients with mandibular skeletal Class II malocclusion - Silva,Nayanna Nadja e (2015)
Objective: Mandibular Class II malocclusions seem to interfere in upper airways measurements. The aim of this study was to assess the upper airways measurements of patients with skeletal Class II malocclusion in order to investigate the association between these measurements and the position and length of the mandible as well as mandibular growth trend, comparing the Class II group with a Class I one.Methods:A total of 80 lateral cephalograms from 80 individuals aged between 10 and 17 years old were assessed. Forty radiographs of Class I malocclusion individuals were matched by age with forty radiographs of individuals with mandibular Class II malocclusion. McNamara Jr., Ricketts, Downs and Jarabak's measurements were used for cephalometric evaluation. Data were submitted to descriptive and inferential statistical analysis by means of SPSS 20.0 statistical package. Student's t-test, Pearson correlation and intraclass correlation coefficient were used. A 95% confidence interval and 5% significance level were adopted to interpret the results.Results:There were differences between groups. Oropharynx and nasopharynx sizes as well as mandibular position and length were found to be reduced in Class II individuals. There was a statistically significant positive correlation between the size of the oropharynx and Xi-Pm, Co-Gn and SNB measurements. In addition, the size of the nasopharynx was found to be correlated with Xi-Pm, Co-Gn, facial depth, SNB, facial axis and FMA.Conclusion: Individuals with mandibular Class II malocclusion were shown to have upper airways measurements diminished. There was a correlation between mandibular length and position and the size of oropharynx and nasopharynx.